To assess dietary habits and associated risk factors among medical students in North Delhi: A major health concern - Pooja Ahlawat; Archana Dwivedi; Nidhi Dwivedi; Gunjan Mahuar; Kamaljeet Singh; Mridul Mahaur; Soumit Sharma; Akshita Jain (Tungs’ Medical Journal)
Background: Medical students are expected to have good dietary habits and to maintain a healthy lifestyle considering their increased knowledge regarding healthy and balanced diets. Although medical students possess high knowledge about healthy dietary habits, they do not practice these habits. Objectives: This study aimed to assess the dietary habits and risk factors associated with poor dietary habits among medical students. Methods: A cross-sectional study using the complete enumeration sampling method was conducted on medical students of North Delhi Municipal Corporation Medical College and Hindu Rao Hospital. A pre-designed pre-tested semi-structured questionnaire was used to collect student data. To assess dietary habits, the World Health Organization-STEPwise approach to the noncommunicable disease risk factor surveillance questionnaire was modified and used. Data were analyzed using Statistical Package for the Social Sciences (version 21). Results: Among the study participants, 31.3% of male students and 31.6% of female students had good dietary habits. Furthermore, 42.7% of the students consumed two main meals a day, whereas only 4.7% consumed one main meal a day. Of the study participants, 47% did not eat meals at regular intervals. Moreover, 41% consumed snacks between the main meals. Most medical students (90.2%) consumed fast food. It was found that 58.2% of the students consumed fruits and vegetables at least once daily. Residence and alcohol consumption were strong predictors of dietary habits. The findings of this study revealed that poor dietary habits were significantly associated with poor-quality sleep. Conclusion: Although medical students possess high knowledge about healthy dietary habits, they do not practice these habits.